The clinical anatomy of the left atrial structures used as landmarks in ablation of arrhythmogenic substrates and cardiac invasive procedures - Damian Dudkiewicz; Katarzyna Słodowska; Katarzyna A. Jasińska; Halina Dobrzynski; Mateusz K. Hołda (Elsevier, 2021)
Background: The clinical anatomy of the left atrium is of special interest since many invasive procedures are performed within this chamber. Pulmonary vein isolation, linear transcatheter ablations, transcatheter mitral valve repair procedures and left atrial appendage occlusions are examples of highly effective procedures done within the left atrial chamber. Methods: This narrative literature review seeks to discuss the latest articles about the anatomy of left atrial structures. Results: This article reviews recent morphological studies about the pulmonary venous ostia, the myocardial sleeves of the pulmonary veins, the mitral isthmus, the left atrial appendage isthmus, the left atrial medial isthmus and the other left atrial isthmuses together with spatial relationships of blood vessels within the isthmus lines. This review touch upon the clinical relevance of the left lateral ridge and the left atrial appendage. Conclusion: A thorough understanding of local anatomy is essential for safe electrophysiologic invasive procedures. Clinical anatomy of the left atrium is treacherous, difficult and its unfamiliarity can cause serious intraoperative complications. Some anatomical features of the left atrium may significantly impede invasive transcatheter interventions, especially ablation procedures.